2003
DOI: 10.1063/1.1624836
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic dispersion in confined packed beds

Abstract: Pore-scale simulations of monodisperse sphere packing and fluid flow in cylinders have reproduced heterogeneities in packing density and velocity previously observed in experiment. Simulations of tracer dispersion demonstrate that these heterogeneities enhance hydrodynamic dispersion, and that the degree of enhancement is related to the cylinder radius, R. The time scale for asymptotic dispersion in a packed cylinder is proportional to R2/D̂T, where D̂T represents an average rate of spreading transverse to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 30 publications
3
50
0
Order By: Relevance
“…For the mean concentration of solute in confined porous media, Hamdan et al even presented an extended high-order model [47], though with complexity beyond reach of practical applications for the time being. Similar operation of average to yield Taylor dispersion is found in studies of a packed bed associated with groundwater pollution and chemical engineering [45,[48][49][50].…”
Section: Velocity Profilementioning
confidence: 80%
“…For the mean concentration of solute in confined porous media, Hamdan et al even presented an extended high-order model [47], though with complexity beyond reach of practical applications for the time being. Similar operation of average to yield Taylor dispersion is found in studies of a packed bed associated with groundwater pollution and chemical engineering [45,[48][49][50].…”
Section: Velocity Profilementioning
confidence: 80%
“…These techniques have also been used to visualize and quantify pore structural changes as a result of biofi lm growth (e.g., Iltis et al 2011) and reactive transport (e.g., Noiriel et al 2005) as shown in Figure 1. For granular media, Monte Carlo (Maier et al 2003), cooperative rearrangement (Thane 2006), and sequential sedimentation (Coelho et al 1997;Øren and Bakke 2002) algorithms are commonly used to digitally reconstruct representations of various grain packs, in which the pore space geometry is well-defi ned. Such reconstructions, although approximations of actual porous media, provide valuable insights into the link between depositional processes (e.g., cementation and compaction) and hydraulic/transport properties (e.g., permeability) of granular media (Bryant et al 1993a,b;Bakke and Øren 1997).…”
Section: Direct Pore-scale Modelingmentioning
confidence: 99%
“…Finally, the transport of point-like tracers in the interparticle void space and porous shells of the packing particles was modeled by a random-walk particle-tracking (RWPT) technique. A similar simulation approach was previously applied to study the effect of packing porosity, morphology, and particle size distribution on effective diffusivity and eddy dispersion in packed beds [25,[27][28][29][30][31]; to analyze the impact of the packing confinement on eddy dispersion [32,33]; to study hydrodynamic dispersion in silica and polymeric chromatographic monoliths [34][35][36][37][38]; and to investigate the influence of analyte retention and adsorption kinetics on mass transport in open channels and packed beds [39][40][41]. In this study, we mainly focus on the analysis of the influence of two core-shell particle characteristics -the shell thickness and the value of the effective diffusion coefficient in the shell -on the plate height.…”
Section: Introductionmentioning
confidence: 99%